Tetrafulgoria, a new generic replacement name for fossil Tetragonidium Bode, 1953 (Insecta: Hemiptera: Fulgoridiidae) non Pascher, 1914 - Doweld, Alexander B. (Zootaxa, 2013)
A new name for the extinct planthopper genus—Tetrafulgoria nom. nov. is proposed to replace preoccupied name Tetragonidium Pascher, 1914 (Protista).